E-091 Treatment of Aneurysms of the Pericallosal Artery with the Pipeline Embolization Device. (29th July 2016) - de Macedo Rodrigues, K; Kühn, A; Tamura, T; Dabus, G; Kan, P; Marosfoi, M; Lozano, J; Howk, M; Perras, M; Brooks, C; Rex, D; Massari, F; et al.
Abstract : Background/objective: Pericallosal artery aneurysm treatment is challenging using traditional endovascular techniques due to the small caliber of the parent vessel and distal access. Wide neck and bifurcation aneurysms in this location require manipulation with 2 catheters for balloon assisted or stent assisted coil embolization with increased friction and limited margin for error. We demonstrate the feasibility, efficacy and safety of endovascular treatment of pericallosal artery aneurysm using flow diversion technology. Methods: We performed a retrospective review of our institutional database from July 2013 through July 2015. Five subjects with a pericallosal artery aneurysm that was treated with the Pipeline embolization device (PED) were identified. We evaluated for technical feasibility, presence of procedural complication, angiographic results, and clinical outcome. Results: Successful placement of a single PED across the neck of the aneurysm was achieved in all cases. No procedure-related complications were encountered. A 6 month follow-up angiogram was available for 4 patients and a 12 month follow-up angiogram was available for 2 patients. Four out of 5 patients had complete aneurysm occlusion demonstrated, 3 of them were demonstrated at the 6 month follow-up and 1 at 12 month follow-up. The subject for which occlusion was demonstrated at the 12 month follow-up did not have a 6 month angiogram available for review. One patient had persistent aneurysm filling at 6 month, with a 50–60% decrease in aneurysm size. There were 2 cases of narrowing of at the origin of an artery that had been coved by the PED, without flow limitation or clinical consequences. There was no evidence of in-stent stenosis or intimal hyperplasia. No thromboembolic or hemorrhagic complication was seen. Modified Rankin scale scores remained unchanged from baseline. Conclusions: Our preliminary results support the use of flow diverter stent for treatment of aneurysms of the pericallosal artery with high rate of aneurysm occlusion, without evidence of increased procedural complication or short-term morbidity. A long-term and larger cohort study is desirable to validate our results. Disclosures: K. de Macedo Rodrigues: None. A. Kühn: None. T. Tamura: None. G. Dabus: None. P. Kan: 2; C; PK is a consultant for Stryker Neurovascular, Covidien, and MicroVention. M. Marosfoi: None. J. Lozano: None. M. Howk: None. M. Perras: None. C. Brooks: None. D. Rex: None. F. Massari: None. M. Gounis: 1; C; NIH, Medtronic Neurovascular, Microvention/Terumo, Cerevasc LLC, Gentuity, Codman Neurovascular, Philips Healthcare, Stryker Neurovascular, Tay Sachs Foundation, and InNeuroCo Inc. 2; C; Codman Neurovascular and Stryker Neurovascular. 4; C; InNeuroCo Inc. A. Wakhloo: 1; C; NIH, Philips Healthcare, Wyss Institute. 2; C; Codman Neurovascular and Stryker Neurovascular. 4; C; co-founder of InNeuroCo Inc. and major stockholder; stocks in EpiEB and Pulsar Medical. 6; C; speaker: Harvard Postgraduate Course, Miami Cardiovascular Institute. A. Puri: 1; C; Stryker Neurovascular and Covidien. 2; C; Codman Neurovascular, Stryker Neurovascular and Covidien. 4; C; InNeuroCo Inc. 6; C; speaker: Miami Cardiovascular Institute.